Translocal Relationships among Associations and Christ Groups, Revisited - Hall, Josiah D. (2022)
In the twenty-five years since Richard Ascough’s article, "Translocal Relationships among Voluntary Associations and Early Christianity," scholarship has largely swung the pendulum away from viewing the translocality of early-Christ groups as an anomaly and using that "uniqueness" as justification for denying the heuristic value of Greco-Roman associations for understanding Christ-groups. A side-effect of this shift, however, has been that scholars often only compare Greco-Roman associations and Christ-groups on the basis of local instantiations. This article, in contrast, recovers a focus on the translocal relationships between associations, examining various motivations for translocal relationships between voluntary associations and showing the heuristic payoff for comparing translocal voluntary associations with early Christ-groups. Additionally, the article concludes that the comparison should work in both directions. That is, the nature of the evidence of the translocality of early Christ-groups actually allows these groups to function as an important heuristic for translocal Greco-Roman associations.
In den 25 Jahren seit Richard Ascough’s Artikel "Translocal Relationships among Voluntary Associations and Early Christianity" hat es einen Umschwung in der Forschung gegeben: Die Translokalität frühchristlicher Gruppen wird nicht länger als eine Anomalie gesehen, womit deren vermeintliche Einzigartigkeit als Argument dafür ausscheidet, den heuristischen Wert der Betrachtung griechisch-römischer Vereine für das Verständnis christlicher Gemeinden zu leugnen. Ein Nebeneffekt dieses Umschwungs ist allerdings, dass griechisch-römische Vereine und Christus-Gruppen häufig nur im Hinblick auf ihre lokalen Ausprägungen verglichen werden. Diese Studie setzt dagegen einen Fokus auf die translokalen Beziehungen zwischen freiwilligen Vereinigungen und zeigt den heuristischen Nutzen des Vergleichs von translokalen freiwilligen Vereinigungen mit frühchristlichen Gruppen. Darüber hinaus kommt die Studie zu dem Schluss, dass der Vergleich in beide Richtungen funktionieren müsste; d.h., die Art und Weise der Translokalität frühchristlicher Gruppen kann als heuristisches Mittel zum Verständnis translokaler griechisch-römischer Vereine dienen.
Keywords: 1 Clement; Christ groups; Romans; translocal; voluntary associations